SHADOW PUPPETS: THE NEGOTIATED CULTURE IN MALAYSIA AND INDONESIA - Dewi Hermawati Resminingayu (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2022)
This paper aims to analyse the cultural dynamics of Malaysia and Indonesia through shadow puppet play. Before the coming of Islam, Srivijaya and Majapahit Kingdoms had ruled most of the current area of Malaysia and Indonesia. These two powerful kingdoms had rooted Indian culture and religion in the region. Thus, it is not surprising that shadow puppets can be found in both countries as the manifestation of Indian culture. Such culture could still exist despite Islam's presence and the establishment of Islamic kingdoms until the colonisation era. However, after Malaysia and Indonesia gained independence, both countries embraced different state ideologies, which affected the existence of shadow puppets. Using the qualitative method, this paper will show how shadow puppet faces political and cultural challenges in both countries. Such challenges lead to changes in shadow puppet play, resulting in the differences in the play in Malaysia and Indonesia.